O software RPG Maker e a construção do jogo Apolo: uma experiência com professores de matemática - Sousa, Rafael Ferreira de Camargos (2018)
With the development and popularization of some technologies such as computer and video games combined with the possible positive entertainment that these instruments can bring to the individual, it would not be difficult to predict that many of these items would reach our students' daily lives and, consequently, our school reality as teachers. In this sense, it becomes increasingly necessary that the teacher understands this movement of insertion of the different technologies in the school context and also seeks to study the possible ways of using these resources to teach and learn mathematics for example. Thinking about this relation of the teacher with the technologies, more specifically with the computer and the construction of digital games, we looked for to analyze the trajectory of a work team formed by two teachers of Mathematics in the construction of a digital game using the software RPG Maker and to respond to next question: How can the process of elaborating a Digital Game contribute to the process of teacher training in Mathematics ?. For the analysis and interpretation of the data the inherent knowledge of the qualitative research was used. They were taken as instruments for data production: the field notes; photographs; filming and interviews. With the analysis of the results obtained from the data produced, it was possible to observe that this construction process brought several positive points for the work team, such as the importance of reflection on the teaching practice, the power of dialogue and listening, to learn from others, and in addition to highlighting points that may be improved in future activities, since we believe that our game is not finished, so we have many elements that can still be edited in order to improve the results of upcoming educational experiences using our digital game.